SERUM FERRITIN LEVELS AS A RISK FACTOR IN TYPE II DIABETES MELLITUS - DR.A.J.MANJULA DEVI,; DR.KALAISELVI.V.S, (International Journal of Pharma and Bio Sciences, 2014)
Diabetes Mellitus is a predominant public health concern, affecting millions of people worldwide. Recently, it has been recognized that, increased body iron stores are associated with Type-2diabetes mellitus. Increased Serum Ferritin have been reported to negatively correlate with insulin sensitivity and the presence of insulin resistance syndrome. The relationship between iron metabolism and type 2 diabetes mellitus is bi-directional. Iron affects glucose metabolism and glucose metabolism impinges on several iron metabolic processes. Iron overload decreases insulin sensitivity and cause earlier complications in diabetes mellitus. This study attempts to evaluate the significance of serum ferritin level as an early predictor of type 2 diabetes mellitus and its relationship with HbA1c.